2007
DOI: 10.1101/gr.6018607
|View full text |Cite
|
Sign up to set email alerts
|

Fusion transcripts and transcribed retrotransposed loci discovered through comprehensive transcriptome analysis using Paired-End diTags (PETs)

Abstract: Identification of unconventional functional features such as fusion transcripts is a challenging task in the effort to annotate all functional DNA elements in the human genome. Paired-End diTag (PET) analysis possesses a unique capability to accurately and efficiently characterize the two ends of DNA fragments, which may have either normal or unusual compositions. This unique nature of PET analysis makes it an ideal tool for uncovering unconventional features residing in the human genome. Using the PET approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 72 publications
1
72
0
Order By: Relevance
“…had previously pioneered pair-end-tag sequencing of full-length cDNA from the MCF-7 transcriptome (Ruan et al 2007). This RNA paired-end-tag (RNA-PET) approach captures the sequence of the ends of full-length transcripts with high sequencing depth and is complementary to the DNA-PET approach for identifying unconventional fusion transcripts.…”
Section: Transcriptional Consequences Of Structural Mutations In Breamentioning
confidence: 99%
See 1 more Smart Citation
“…had previously pioneered pair-end-tag sequencing of full-length cDNA from the MCF-7 transcriptome (Ruan et al 2007). This RNA paired-end-tag (RNA-PET) approach captures the sequence of the ends of full-length transcripts with high sequencing depth and is complementary to the DNA-PET approach for identifying unconventional fusion transcripts.…”
Section: Transcriptional Consequences Of Structural Mutations In Breamentioning
confidence: 99%
“…To identify further FG and 39T-derived transcripts in MCF-7, we intersected DNA-PET data with GIS-PET and RNA-PET data. GIS-PET data sets for MCF-7 were described previously (Ng et al 2006;Ruan et al 2007). We compared 59 fused gene symbols of FG and 39T predicted in the DNA-PET data and those of the transcriptome data.…”
Section: Intersection Of Dna-pet and Gis-pet/rna-pet In Mcf-7mentioning
confidence: 99%
“…To predict putative TSSs in silico, we first used published data that describe human transcribed sequences, such as full-length cDNAs and 59-end cDNA sequence tags (Carninci et al 2005;Ruan et al 2007;Wakaguri et al 2007), which specify TSSs when aligned to the genome. We aligned a database of more than 250,000 human cDNAs and predicted about 37,000 gene models, with about 22,000 gene models represented by two or more cDNAs.…”
Section: Promoter Activity and Gene Expression Datamentioning
confidence: 99%
“…Studies in yeast (Saccharomyces cerevisiae; David et al, 2006), animals (Bertone et al, 2004;Carninci et al, 2005), and plants (Yamada et al, 2003;Li et al, 2007;Matsui et al, 2008) have revealed the presence of a large number of unannotated, novel transcripts. These novel transcripts may represent alternatively spliced forms of known genes (Filichkin et al, 2010), products of antisense (Yamada et al, 2003) or bidirectional transcription (Xu et al, 2009), retained introns (Ner-Gaon et al, 2004;Filichkin et al, 2010), transcript fusions (Ruan et al, 2007), or intergenic transcriptional units (referred to hereafter as intergenic transcribed fragments [ITFs]). Among these novel transcripts, ITFs are unique in that they do not overlap with known genomic features and may represent novel genic sequences.…”
mentioning
confidence: 99%